Community Development Banking At PT. Bank Negara Indonesia, Tbk - Astuti, Susi (Jurnal Inovasi Pengabdian Masyarakat, 2024)
Community development activities carried out by PT. Bank Negara Indonesia, Tbk has an important role in efforts to develop a sustainable and active community condition based on the principles of social justice and mutual respect. Banking seeks to facilitate citizens in the process of creating social justice and mutual respect through broad development programs that connect all components of society. Community development translates the values of openness, equality, responsibility, opportunity, choice, participation, mutual benefit, reciprocity and continuous learning. The essence of community development is education, making community members capable of doing something by providing the necessary strength or means and empowering the community. The methods used in this community service activity are experiential learning and counseling. The aim of this community service activity is to provide a review of the theory and implementation of Corporate Social Responsibility in the form of community development activities. The conclusion of this community service activity is the achievement of company goals through the implementation of community development programs.